Social Media as a Political Platform in Africa: A Bibliometric Analysis - Hussein Gibreel Musa; Ana kumalasari; Alnour Abobaker Mohamed Musa (Komunikator, 2023)
This study employs bibliometric analysis to scrutinize the pivotal journals, institutions, and countries at the nexus of social media and political discourse in Africa. Utilizing VOSviewer, a dataset of 123 publications from 2013 to 2023 was culled from Scopus Database. The analysis encompasses diverse methodologies, each tailored to the specific nature of bibliometric investigation. "Information, Communication and Society" emerged as the foremost journal in this domain, while South Africa spearheaded contributions, followed by the United States and the United Kingdom. The National Research Foundation played a prominent role as an influential institution. Notably, four distinct thematic clusters emerged, illuminating significant research areas such as the role of political platforms on human rights, the influence of social media on community engagement, the impact of media platforms on African conflicts, and social media's contribution to freedom through discourse. This study represents a pioneering bibliometric endeavor in comprehensively gauging the landscape of social media and politics in Africa, offering valuable insights for scholars and policymakers navigating this dynamic terrain.